Surgery in Varicose Veins - Hussein, Hassanein A.; Hussen, Waleed M. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Varicose veins are common in Iraq. Increasing incidence is associated with available jobs of bodyguards, barbers and computer workers.Objectives: To highlight the frequency, presentation, methods of accurate diagnosis and surgical procedures which are commonly used by Vascular Surgeons in Medical City Teaching Complex, Al-Shaheed Ghazi Al-Hariri Subspecialties hospital and to compare this study with other international studies.Patients and methods:  This is a retrospective study of hundred patients with varicose veins, who were admitted and surgically treated at Al-Shaheed Ghazi Al-Hariri subspecialties hospital during one year period (1st of July 2010 to the 30th of June 2011). It illustrates the technique used and presents the surgical complications met within these cases.Results: Most of the patients were males (67%). Most of them were bodyguards or computer workers. In eight patients only surgical complications are met and dealt with.Conclusions: We are in utmost need for newer methods of treating varicose veins such as Endovenous laser treatment or radiofrequency ablation, and also in need for a well trained personnel and the essential equipments to implicate this.